Carvacrol, citral, eugenol and cinnamaldehyde casein based edible nanoemulsions as novel sustainable active coatings for fresh pork tenderloin meat preservation - Zaharioudakis, Konstantinos; Salmas, Constantinos E.; Andritsos, Nikolaos D.; Kollia, Eleni; Leontiou, Areti; Karabagias, Vasillios K.; Karydis-Messinis, Andreas; Moschovas, Dimitrios; Zafeiropoulos, Nikolaos E.; Avgeropoulos, Apostolos; Proestos, Charalampos; Giannakas, Aris E. (Frontiers in Food Science and Technology, 2024)
Introduction: Nowadays, the bioeconomy and sustainability trends drive the food sector to replace chemical preservatives with bioactive compounds recovered from biomass such as essential oils (EOs) and their derivatives. Moreover, nanotechnology trend drives food sector in the nanoencapsulation of such bioactive compounds in novel edible formulations such as nanoemulsions to enhance their controlled release properties, their bioactivity and their biocompatibility. Methods: In this study the development and characterization of novel casein/lecithin (CSN/LCN) based nanoemulsions (NEs) with carvacrol (CV), cinnamaldehyde (CI), citral (CT), and eugenol (EG) as nanoencapsulated oil phase is presented as well as the application of such NEs as active coatings for the preservation of fresh pork tenderloin. Results and discussion: DLS measurements as well as TEM images showed an average particle size distribution of 20–40 nm for all obtained NEs, while z-potential results indicate their physicochemical stability. All the obtained NEs needed at least 5 times less amount of EOs derivatives to scavenge 50% of radicals and demonstrated a higher antibacterial activity against Escherichia coli and Listeria monocytogenes compared to free EOs derivatives. Pork fresh tenderloin meat treated with NEs demonstrated 30% higher efficacy in obtained lipid oxidation values than uncoated pork meat samples and 12% higher efficacy in obtained lipid oxidation values than pork meat samples treated with EOs derivatives. From a microbiological point of view NEs manage to extend pork tenderloin meat shelf life by 6 days compared to uncoated pork tenderloin meat and by 3 days compared to tenderloin pork meat coated with free EOs derivatives. Lab* colorimetry analysis as well as sensory analysis revealed that such edible CSN/LCN based NEs succeeded to preserve the texture, appearance, and color of pork tenderloin meat in higher acceptance limits compared to the corresponding characteristics of pork tenderloin meat coated with free EOs derivatives. Overall, the current study suggests novel CSN/LCN-based edible NEs as a promising technology that can be used as edible active coatings in the meat food industry.